Rules of the Sunlight Sick, Funeral and Medical Aid Society - Leverhulme, William Hesketh Lever, Viscount, 1851-1925 (1909)
1909 1909 1900s 10 pages XX. APPENDIX. rural areas. A strip down the centre roadway of 15 to 18 feet wide properly pitched and macadamized for vehicular traffic and strips 4 feet wide, flagged or gravelled for footpaths down each side, the remainder of the roadway and footpaths being finished in grass with, if possible, an avenue of trees on each side will be found to be the cheapest and best form of road construction. Houses should be built a minimum of 15 feet from the roadway and 25 feet or more where practicable, every house should have a space available in the rear for vegetable garden. Open spaces for recreation should be laid out at frequent and convenient centres. There is no difficulty in providing these conditions. Even taking the area of London, I find that these conditions could be enjoyed to-day if proper distribution of houses on the land within the area had been made. The metropolitan area of London is 74,839 acres, with a population of 4,536,541, which is at the rate of 12 houses to the acre, each house containing five persons. The fact is we do our town planning after the mode of badly packed trunks. We all know that one's wardrobe badly packed in a trunk is spoiled, and the trunk appears all too small for what it has to hold. But our wardrobe carefully folded and the same trunk holds all that is required, without damage, and with greater convenience of access. Our bye-laws already limit the number of lodgers allowed in a lodging house and there should be bye-laws restricting the number of houses to the acre. If this is done and a relaxation of the building conditions as to the material to be used, permitting a greater range of selection of building material, thus reducing the heavy expense of building and of roadmaking to what is absolutely reasonable and necessary, then not only will building become cheaper and roadmaking cheaper, but infinitely superior in quality. Less elaboration in architectural effects would be needed to make a beautiful city, town or village than under present conditions; a few sprays of ivy and a greensward in front of a house, a shrub here and there, and the plainest and most economical cottage, architecturally, becomes more beautiful than a more costly one and elaborate one built right on the edge of the footpath without any intervening fringe of greensward. A home requires a greensward and garden in front of it just as much as a cup requires a saucer or a hat the brim. Dust nuisance from passing traffic would be reduced in all such homes and the conditions of living would become healthy and happy. At Port Sunlight efforts have been made to carry out these conditions with what success you will be better able to judge than ourselves. I thank you for the patience with which you have listened to me, and hope you may have long life and happiness to continue in the enjoyment of your labours for housing reform. RULES OF THE Sunlight Sick, Funeral and Medical Aid Society. NAME, OBJECT, AND PLACE OF OFFICE OF THE SOCIETY. I.— That this Society be called the SUNLIGHT SICK, FUNERAL AND MEDICAL AID SOCIETY. That its object be to raise a Fund by subscription from its members, or otherwise, as the Committee may direct, for the purpose of providing medical attendance (when in the Medical Officer's district), medicine, sick allowance, and payment on death of members, their wives, and children under fourteen years of age. And that its place of office be at PORT SUNLIGHT, CHESHIRE. VOTES AND MODE OF VOTING. II.— Each member shall have one vote only in the determination of any question brought before a meeting, and in the election of officers one vote for each of as many candidates as are required to make up the list. The electiou of officers and any questions as to the Rules shall be decided by ballot, and a majority at any meeting may also decide that any other questions shall be determined by ballot. No member shall have any right to vote at any meeting of the Society or Committee unless he is clear on the books of the Society, and has been a member for at least 8 weeks. Members in Class A (Juniors) are not entitled to vote, or take any part in the business of the Society. MANAGEMENT. III.— The management of the Society shall be vested in a Committee consisting of one representative from each recognized department, elected annually by ballot; they must be chosen from those members over 21 years of age, who have been members for at least 6 months. Nomination papers shall be posted on the Notice Boards 14 clear days prior to the Annual General Meeting, and shall not be removed until within 3 clear days of such Annual General Meeting. Candidates for Committee receiving the largest number of votes shall be declared elected, but in the event of two or more persons working at the same trade or in the same department, only the one receiving the highest number of votes shall be declared elected. The Committee shall meet monthly on a night to be settled at the first meeting of each new Committee. One quarter the total number of the Committee to form a quorum. Retiring members are eligible for re-election. The Committee shall have power to remove any official of the Society at any time on satisfactory proof of misconduct or wilful neglect of duty, and any official shall deliver up all property he may have in his possession belonging to the Society when required to do so by them. The Secretary to be convener of the meetings. CHAIRMAN AND VICE-CHAIRMAN IV.— These shall be elected by the Committee at their first meeting after the Annual General Meeting, and shall continue in office throughout the year. The Chairman shall preside at all meetings of Committee. TREASURER. V.— The Treasurer shall be elected by the Committee at the first meeting after the Annual General Meeting, and shall continue in office throughout the year. He shall prepare a half-yearly statement, and yearly Balance Sheet, duly audited and passed by the Committee. SECRETARY. VI.— There shall be a Secretary elected annually by ballot at the Annual General Meeting, who shall receive as salary 3 per cent. per annum on all contributions, fines, and levies collected. Payment thereof shall be made by quarterly instalments. The Secretary shall appoint a suitable person to assist him when necessary, and the remuneration for this assistance shall be according to work done, to be paid by the Secretary out of the 36/H24/20